Moving with and Without Music: Scaling and Lapsing in Time in the Performance of Contemporary Dance - Stevens, C.; Schubert, E.; Wang, S.; Kroos, Christian; Halovic, S. (University of California Press, 2009)
TIME-KEEPING AMONG DANCERS WAS INVESTIGATED by measuring a dancer's movement in the presence and absence of music. If an internal clock was at work, then change from the ideal would manifest as scaling---consistently faster or slower unaccompanied performance; if time differences were due to lapsing, then sections from the with-music condition would be deleted, or material would be inserted into the no-music condition. Motion was recorded during ensemble performances of a four-minute choreographed piece with and without music. The median of 24 markers in the height dimension was analyzed for scaling and lapsing. Twenty percent of the variance was accounted for by sporadic scaling. Lapses---insertions and deletions---accounted for nearly all the speeding up---10.45 of 14 s. As in musical performance of memorized material, lapsing rather than scaling accounted for timing variations. Automation of lapsing and scaling detection has application in the analysis of music and dance time series data.